PELATIHAN PENYUSUNAN PENELITIAN TINDAKAN KELAS BAGI GURU AGAMA BUDDHA DI KABUPATEN BOYOLALI - Rispatiningsih, Dwi Maryani; Sujiono, Sujiono; Purnomo, Danang Try; Sudarto, Sudarto; Shadikah, Arina Afiyati; Harto, Sugik (Jurnal Pengabdian Masyarakat Polmanbabel, 2024)
Professional teachers are those who can carry out classroom action research (PTK) and other research as supporting elements. Various types of research carried out by teachers have the hope that improving learning activities will create better learning. Teachers are not always concerned with learning administration alone, but teachers must also be able to identify problems with their students. Community service activities carried out by lecturers at the Sekolah Tinggi Agama Buddha Negeri Raden Wijaya Wonogiri use material presentations and assistance to Buddhist teachers in Boyolali. Apart from lectures, the service team also provided a questionnaire to measure the level of teacher understanding regarding Classroom Action Research in implementing service activities. The results of the service carried out show that with an increase in understanding of the equipment presented by the service team and the assistance provided, Buddhist teachers can prepare PTK for 90% of the total participants in training activities for preparing for Classroom Action Research.